Segetal plants of agricultural landscapes of the Southern Non‐Chernozem zone as a source of biological resources - A. N. Nikolskii; V. D. Bochkarev; D. V. Bochkarev; K. O. Drozdova (Юг России: экология, развитие)
Aim. To identify economically significant species of segetal plants of agrophytocenoses in the Southern Non‐Chernozem zone and assess their dynamics with changes in anthropogenic load.The study was carried out by analysing geobotanical descriptions of agrophytocenoses in the Southern Non‐Chernozem Zone. The species diversity of economically important species was established during the period of extensive farming (1929–1933), the beginning of intensification (1936–1938), a high level of intensification (1981–1983), and a period of decreasing intensity of farming (2012–2022).At all stages of the study, groups of forage, medicinal and honey plants were round to have a high species diversity. The presence of individual representatives of vegetable, vitamin, insecticidal and ornamental species in agrophytocenoses was established.Changes in the nature and degree of anthropogenic pressure on agrophytocenoses has led to a significant transformation of species composition and abundance of representatives of economically significant groups. The smallest number of these was noted in the 1980s. Currently, species diversity has increased due to a decrease in the intensity of agriculture in the region.